CONVERSATIONAL IMPLICATURE OF THE PRESENTERS IN TAKE ME OUT INDONESIA - Nanda, Sheila; Sukyadi, Didi; Ihrom, Sudarsono Muhammad (Indonesian Journal of Applied Linguistics, 2012)
Abstract: In the past few years, game shows such as Take Me Out Indonesia were quite popular in Indonesian television. These game shows were quite interesting to study because they were not only involving many participants, but also requiring the settings in which politeness and implicature needed to be used to keep the communication flows smoothly. This paper is a pragmatic study that aims at investigating conversational implicature that the presenters of Take Me Out Indonesia operate within their utterances along with the possible implications that lie behind the implicature[AJ1] . The episode XXII of the show was chosen purposively as the sample. Qualitative method was employed in processing the transcription of the 204 recorded implicature data. The intended features were identified, classified, calculated and then separately analyzed based on conversational implicature theory proposed by Grice (1975). The result shows that the presenters tended to use generalized conversational implicature (59, 8%) rather than the particularized (40,2%). Based on the functions, inferences or motive it contains, generalized conversational implicature can be classified into ten categories implying: (1) the presence of the opposition, (2) the invalidity of the expressions or events at the time of speaking, (3) â€œnot allâ€, (4) events that have not yet occured, (5) the actual position, (6) persons or things having similararity, (7) â€œnot completelyâ€, (8) further actions, (9) the others of the similar kind, and (10) the opposite of the real situations. The needed inferences fall into two classifications: (1) the showâ€™s settings inferences and (2) general knowledge inferences. Based on the objectives, particularized implicatures are used to ensure: (1) the effectiveness of a polite criticism, (2) maximum efficiency of communication, (3) minimum degree of an imperativeâ€™s imposition, and (4) alleviation of otherâ€™s self offensiveness. This study concludes that various types of implicature were used in informal game show conversation to make interaction flows smoothly. Â  Key words: conversational implicature, maxims, inference, meanings, game show s. Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â